Comparative experimental and simulation studies of high-power AlGaN-based 353 nm ultraviolet flip-chip and top-emitting LEDs. (5th February 2018) - Liu, Mengling; Zhou, Shengjun; Liu, Xingtong; Gao, Yilin; Ding, Xinghuo
Abstract: Experimental and simulation studies of high-power AlGaN-based 353 nm ultraviolet (UV) flip-chip (FC) and top-emitting (TE) light-emitting diodes (LEDs) are performed here. To improve the optical and electrical properties of ultraviolet LEDs, we fabricate high-power FC-UV LEDs with Ta2 O5 /SiO2 distributed Bragg reflectors (DBRs) and a strip-shaped SiO2 current blocking layer (CBL). The reflectance of fourteen pairs of Ta2 O5 /SiO2 DBRs is 96.4% at 353 nm. The strip-shaped SiO2 CBL underneath the strip-shaped p-electrode can prevent the current concentrating in regions immediately adjacent to the p-electrode where the overlying opaque p-electrode metal layer absorbs the emitted UV light. Moreover, two-level metallization electrodes are used to improve current spreading. Our numerical results show that FC-UV LED has a more favorable current spreading uniformity than TE-UV LED. The light output power of 353 nm FC-UV LED was 23.22 mW at 350 mA, which is 24.7% higher than that of TE-UV LED.